2018
DOI: 10.1177/1945892418813079
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine in Chronic Rhinosinusitis: A Systematic Review and Qualitative Analysis

Abstract: Background Complementary and alternative medicine (CAM) is frequently used in the treatment of chronic rhinosinusitis (CRS) in developed countries. With a plethora of CAM therapies available, their effectiveness and safety are poorly understood in the context of CRS. Objectives This article aims to critically appraise the evidence for CAM use in CRS through a systematic review of current literature that investigate the effects of CAM on symptoms and clinical status of adults with CRS. Study Design Systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…23 Some alternative therapies show promise as potential treatments for CRS, compared with placebo or as adjuncts to usual care, but based on the limited quality data there is scarce evidence to support the use of homeopathy in CRS. 24 Homeopathy research on sinusitis comprises both acute and chronic conditions. No systematic reviews or metaanalysis could be identified on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…23 Some alternative therapies show promise as potential treatments for CRS, compared with placebo or as adjuncts to usual care, but based on the limited quality data there is scarce evidence to support the use of homeopathy in CRS. 24 Homeopathy research on sinusitis comprises both acute and chronic conditions. No systematic reviews or metaanalysis could be identified on the subject.…”
Section: Introductionmentioning
confidence: 99%